Ulcer in the Disguise-A Rare Case Report - Ipsita Mohanty; Swagatika Panda; Neeta Mohanty; Radhaprasanna Dalai (Institute of Medico-legal Publications Pvt Ltd, 2021)
Tuberculosis (Tb) is an infectious disease which usually affects the pulmonary system and sometimes occursin other body organs including the oral cavity. The present article is on a case study of a 25-year femalediagnosed with TB osteomyelitis which presented a non-healing and non-painful ulcer both intra and extraorally. The diagnosis was confirmed based on histopathology. The patient underwent anti-TB therapy andher oral and systemic conditions improved rapidly. Although oral manifestations of tuberculosis are rare,clinicians should include them in the differential diagnosis of various types of oral ulcers. An early diagnosiswith prompt treatment can prevent complications and potential contaminations. Tuberculosis of the oralcavity is rare and have become a forgotten diagnosis of oral lesions. Dental practitioners need to be awarethat TB may occur in the oral cavity and should be considered in the differential diagnosis of any ulcerated,indurated non-healing lesion of the oral cavity, especially in lower socioeconomic groups. Besides, effortsshould be made to control oral TB by early detection and referral of the patient to a physician for propermanagement. Clinicians are to be careful about ulcers in disguise.